Muscle from grass- and grain-fed cattle differs energetically. (March 2020) - Apaoblaza, A.; Gerrard, S.D.; Matarneh, S.K.; Wicks, J.C.; Kirkpatrick, L.; England, E.M.; Scheffler, T.L.; Duckett, S.K.; Shi, H.; Silva, S.L.; Grant, A.L.; Gerrard, D.E.
Abstract: Insufficient acidification results in dark, firm, and dry beef. While this defect is often indicative of a stress event antemortem, muscle tissue may change in response to feeding regime. Longissimus dorsi muscle samples from 10 grain-fed and 10 grass-fed market weight, angus-crossbred beef cattle were collected postmortem. Lower ( P < .05) L* and a* values were recorded for steaks from grass-fed cattle. Higher ( P < .05) ultimate pH values were noted in lean of grass-fed cattle compared to grain-fed cattle, yet differences in lactate, glycogen and glucose were not detected. Further, increased ( P < .05) ultimate pH values and lower ( P < .05) lactate accumulations were noted when samples from grass-fed cattle were subjected to an in vitro glycolysis system. Muscle from grass-fed beef possessed nearly two-fold more ( P < .05) succinate dehydrogenase and ( P < .001) myoglobin than that of grain-fed cattle. These data show lean from grass-fed beef has greater enzymes reflective of oxidative metabolism and suggest dark lean from grass-fed cattle may be a function of more oxidative metabolism rather than a stress-related event antemortem. Highlights: Grain-fed beef had higher L* and a* values than that of grass-fed beef. Grass-fed beef had higher ultimate pH than that of grain-fed beef. Muscle of grass-fed beef was more oxidative than that of grain-fed beef. Myoglobin abundance was increased in grass-fed beef compared to grain-fed beef.